Association of adiponectin polymorphisms with the risk of diabetic nephropathy in type 2 diabetes: A meta‐analysis 脂联素基因多态性与2型糖尿病肾病的相关性：一项meta分析. (15th July 2014) - Cai, Yuli; Zeng, Tianshu; Chen, Lulu
Abstract Objective Adiponectin gene polymorphisms have been reported to be associated with the risk of diabetic nephropathy (DN) in type 2 diabetes mellitus (T2DM) patients. However, the results are inconsistent. Methods Electronic literature databases and reference lists of relevant articles published until December 2013 were searched as part of a systematic review and meta‐analysis to clarify the association between adiponectin gene polymorphisms and DN susceptibility in T2DM. Fixed‐ or random‐effects models were used to calculate the effect sizes of odds ratio (OR) and 95% confidence intervals (95%CI). Results Eleven case control studies were included. Overall, a significant association was observed for rs2241766T/G polymorphisms under the recessive model (GG vs TT+TG: OR 1.75; 95% CI 1.09–2.80; P = 0.02). For rs17300539G/A, a significant association was observed under the GA vs GG model (OR 1.74; 95% CI 1.13–2.68; P = 0.01) and A vs G allele model OR 1.65; 95% CI 1.13–2.41; P = 0.009). After stratification by ethnicity, we found that the rs2241766 T/G dominant model (GG+TG vs TT: OR 1.52; 95% CI 1.12–2.07; P = 0.007), heterozygous model (TG vs TT: OR 1.52; 95% CI 1.01–2.27; P = 0.04) and G vs T allele (OR 1.50; 95% CI 1.07–2.10; P = 0.02) may be associated with DN risk in the Caucasian population. For rs17300593G/A, the dominant model (GA+AA vs GG: OR 1.75; 95% CI 1.15–2.67; P = 0.009) may be associated with DN risk in the Caucasian population. Conclusion Adiponectin rs2241766T/G and rs17300593G/A rather than rs1501299G/T and rs266729C/G polymorphisms were associated with the risk of DN in T2DM, especially in the Caucasian population.